Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales